Application of community – engaged dissemination and implementation science to improve health equity - Chelsey R. Schlechter; Guilherme Del Fiol; Cho Y. Lam; Maria E. Fernandez; Tom Greene; Melissa Yack; Sandra Schulthies; Marci Nelson; Claudia Bohner; Alan Pruhs; Tracey Siaperas; Kensaku Kawamoto; et al. (Preventive Medicine Reports, 2021)
Community engagement is critical to accelerate and improve implementation of evidence-based interventions to reduce health inequities. Community-engaged dissemination and implementation research (CEDI) emphasizes engaging stakeholders (e.g., community members, practitioners, community organizations, etc.) with diverse perspectives, experience, and expertise to provide tacit community knowledge regarding the local context, priorities, needs, and assets. Importantly, CEDI can help improve health inequities through incorporating unique perspectives from communities experiencing health inequities that have historically been left out of the research process. The community-engagement process that exists in practice can be highly variable, and characteristics of the process are often underreported, making it difficult to discern how engagement of community partners was used to improve implementation. This paper describes the community-engagement process for a multilevel, pragmatic randomized trial to increase the reach and impact of evidence-based tobacco cessation treatment among Community Health Center patients; describes how engagement activities and the resulting partnership informed the development of implementation strategies and improved the research process; and presents lessons learned to inform future CEDI research.